A point-of-care testing assay for clonorchiasis using a EuNPs-CsTR1 fluorescent probe-based immunoassay. - Xiaoxiao Ma; Huiyuan Zhang; Yiming Fang; Jing Wang; Xingyang Wang; Chen Li; Xiaolei Liu; Mingyuan Liu; Bin Tang; Yi Liu (Public Library of Science (PLoS), 2024)
Clonorchis sinensis is one of the most important fish-borne zoonotic parasitic worms in humans, and is distributed in several countries with more than 15 million people infected globally. However, the lack of a point-of-care testing (POCT) method is still the critical barrier to effectively prevent clonorchiasis. With the application of novel fluorescent nanomaterials, the development of on-site testing methods with high signal enhancement can provide a simple, precise and inexpensive tool for disease detection. In this study, Eu-(III) nanoparticles (EuNPs) were used as indicative probes, combined with C. sinensis tandem repeat sequence 1 (CSTR1) antigen to capture specific antibodies. Afterward, the complex binds to mouse anti-human IgG immobilized on the test line (T-line) producing a fluorescent signal under UV light. The EuNPs-fluorescent immunoassay (EuNPs-FIA) was successfully constructed, allowing sample detection within 10 min. It enabled both qualitative determination with the naked eye under UV light and quantitative detection by scanning the fluorescence intensity on the test line and control line (C-line). A total of 133 clinical human sera (74 negative, 59 clonorchiasis, confirmed by conventional Kato-Katz (KK) methods and PCR via testing fecal samples corresponding to each serum sample) were used in this study. For qualitative analysis, the cut-off value of fluorescence for positive serum was 31.57 by testing 74 known negative human samples. The assay had no cross-reaction with other 9 parasite-infected sera, and could recognize the mixed infection sera of C. sinensis and other parasites. The sensitivity and specificity of EuNPs-FIA were both 100% compared with KK smear method. Taking advantage of its high precision and user-friendly procedure, the established EuNPs-FIA provides a powerful tool for the diagnosis and epidemiological survey of clonorchiasis.